Recognize everyone's duty of reasonable care to student‐athletes. Issue 10 (January 2015) - Neal, Timothy; Quandt, Eric; Thornton, James; Anderson, Jeffrey
<x xml:space="preserve">Abstract</x> Athletic trainers, team physicians, coaches, athletics directors, and senior administrative staff — as well as the institution — each face potential liability for the overall health care provided to student‐athletes.